A Theoretical Approach Towards Designing InfoVis for Decision Support Effectiveness - Akanmu, Semiu A.; Jamaludin, Zulikha (Universiti Teknikal Malaysia Melaka, 2017)
t—Information Visualization (InfoVis) as information systems used in gaining insights of large and multidimensional dataset has gained interest of human computer interaction researchers.The researchers have also craved for more theorybased design models to support designing InfoVis and to enhance its decision support effectiveness.This is a result of the observed insufficiency in the theoretical explanation and model of InfoVis design generally, and its decision support effectiveness, specifically.Extant literature reviewed showed that there is lack of studies that explicitly state the linkage between InfoVis design techniques and respective supporting theories, and how this translate to decision support design of InfoVis.This study therefore employs an unobtrusive research method that involves thematic analysis of InfoVis design and related theoretical literatures, to characterize, categorize and link the InfoVis theories with their respective design techniques.The result is a proposed theoretical design model.The model is therefore used, as a validation process, in the design of StudentViz – an InfoVis to support the multidimensionality of students’ dataset.